The Utilization of Wild Animals in Mubri Wariori Village, Manokwari West Papua - Denisa Melanesia Kreglika Taran; Saremay Max Romario Sawaki; Fransiskus Hernandes Taran; Robi Bomoi (Badan Penelitian dan Pengembangan Provinsi Papua Barat, 2022)
The utilization of wild animals to meet human needs has existed throughout history. This study aims to identify the utilization of wild animals by in Mubri Wariori village, the trend of wild animals’ utilization during the Covid-19 pandemic and the conservation programs that are applied to the wild animal populations by the hunters and the community in Mubri Wariori village. The data were collected through open interviews to seven respondents. The Snowball sampling technique was used to determine the respondents. The respondents are all the people who hunt wild animals in the village. The data was analysed descriptively. The result revealed that there are 13 species of wild animals that have been utilized by the hunters and the community in Mubri Wariori. The wild animal is mostly used for household consumption, sold for cash and other usages. This knowledge has been passed down from generation to generation. The respondents have a good understanding of the Covid-19 disease cause and the possibility of some diseases coming from their interaction with wild animals. During the Covid-19 pandemic, market demand for wild animals has increased. Thus, the respondents hunt more frequent, from once a week to five times a week. However, the respondents do not wear protective equipment such as gloves and mask in the process of handling wild animals. The ways that according to the respondents are effective in killing bacteria and viruses are by washing hands and boiling the wild animals’ meat for a long time. Moreover, the respondents and the community has realized the importance of wild animals’ conservation and has implemented conservation efforts for the bird of paradise and turtles.